A concise review on buckwheat materials based ready to serve and ready to eat food products. (2022) - Govindhaswamy Krishnaswamy, Gomathi; Parameshwari, S.
Abstract: Healthy food materials and appropriate lifestyle practices have gained consumer focus over foods with functionality. Buckwheat, a pseudo-cereal with improved nutritional quality as an alternative to traditional cereals like wheat and corn can be exploited to meet the demands on gluten-free ready to serve and ready to cook products. Experimental studies on animals and humans have proved that buckwheat flour alleviates metabolic disorders. High biological value of protein and treasure of nutraceuticals in buckwheat arose interest to review the utility of buckwheat in ready to serve and ready to cook foods. Several buckwheat food materials produced including baked (bread, cookies, cakes and biscuits), fermented (milk, honey, beverage and beer) and other (tea, kasha, tarhana, noodles, pasta and porridge) are at both beta-analysis stage and commercial market. However, subjective and objective evaluations are significant for consideration. Thus, the present study aims to review the nutritional, sensory and functional properties of buckwheat and the potential of buckwheat grains to serve as a raw material for formulation of functional foods through extensive literature search on PubMed and Google search engines.